The narrative sequence as a minimal narratological unit and the narratological descriptors of the fantastic - Remorini, Paolo (Romanica Olomucensia, 2025)
This paper is a contribution to the debate concerning the narrative sequence, defined here as the minimal narratological unit that covers both the narrative discourse (the sjuzhet), through the distinct narratological categories, and the narrated story (the fabula), through the narrative moments and functions, thus reflecting its essential attributes (linearity, unidirectionality, intersequentiality). To that end, the short stories Un volto umano by Tommaso Landolfi (1971) and Lontano lontano lontano (una storia vera) by Michele Mari (2012) were analysed, reporting for each sequence the corresponding descriptors of the narratological categories taken into account and identifying each change in sequence with each change in any of the descriptors involved. Considering how no traditional narratological categories succeed in shedding light on the fantastic nature of the narratives that were analysed, we point out among the results the need to resort to the analytical scheme of the theory of apperceptions on fantastic linkages as a narratological marker of fantastic elements. Therefore, an update of the concept of the narrative sequence as a minimal narratological unit, a theoretical synthesis of the odd works of recent decades, is regarded as essential, and at the same time makes it possible to identify a coherent and reproducible analytical tool of great practical use in the literary analysis of narrative texts.
Keywords: apperception theory; fantastic; Michele Mari; narrative sequence; Tommaso Landolfi